On the theory of the Beltrami equation - Ryazanov, V.I.; Srebro, U.; Yakubov, E. (Український математичний журнал, 2006)
We study ring homeomorphisms and, on this basis, obtain a series of theorems on existence of the so-called ring
solutions for degenerate Beltrami equations. A general statement on the existence of solutions for the Beltrami
equations is formulated extending earlier results. Вивчаються кільцеві гомеоморфізми, i на цій підставі отримано низку теорем про існування так званих кільцевих розв'язків вироджених рівнянь Бельтрамі. Сформульовано загальне твердження про існування розв'язків рівнянь Бельтрамі, що узагальнює більш ранні результати.